Existence of Equilibria in Exhaustible Resource Markets with Economies of Scale and Inventories - Antoine Bommier; Lucas Bretschger; François Le Grand (ETH Zurich, CER-ETH - Center of Economic Research, 2014)
The paper proves the existence of equilibrium in nonrenewable resource markets when extraction costs are non-convex and resource storage is possible. Inventories flatten the consumption path and eliminate price jumps at the end of the extraction period. Market equilibrium becomes then possible, contradicting previous claims from Eswaran, Lewis and Heaps (1983). We distinguish between two types of solutions, one with immediate and one with delayed build-up of inventories. For both cases we do not only characterize potential optimal paths but also show that equilibria actually exist under fairly general conditions. It is found that optimum resource extraction involves increasing quantities over a period of time. What is generally interpreted as an indicator of increasing resource abundance is thus perfectly compatible with constant resource stocks.
Keywords: Q30; C62; D92; D41; 330; Exhaustible resources; nonconvex extraction cost; equilibrium existence; resource storage; Erschöpfbare Ressourcen; Rohstoffvorkommen; Rohstoffwirtschaft; Kosten; Rohstoffpreis; Skalenertrag; Allgemeines Gleichgewicht; Theorie